Effects of Injection Strategies on Mixture Formation and Combustion in a Spark-Ignition Engine Fueled with Syngas-Biogas-Hydrogen - Thanh Xuan Nguyen-Thi; Thi Minh Tu Bui (International Journal of Renewable Energy Development, 2023)
The paper presents the effects of blend injection and dual injection strategies on mixture formation and combustion of syngas-biogas-hydrogen fueling engine working in the solar-biomass hybrid renewable energy system. The research was performed by simulation method on a retrofitted Honda GX200 spark-ignition engine. The results show that at the end of the compression process, in the case of blend injection of 50% syngas-50% biogas, the fuel-rich zone was positioned on the top of the combustion chamber, whereas in the case of dual injection, this zone was found on the top of the piston. In the case of 50% syngas-50% hydrogen supplied, at the end of the compression process, the fuel-rich area observed on the top of the piston with slightly deflected towards the inlet port in both cases of blend and dual injection. When shifting from blend injection mode to dual injection mode, in the case of 50% syngas-50% biogas fueling engine, the mean temperature of the exhaust gas decreased from 1208 K to 1161 K and the NOx concentration decreased from 1919 ppm to 1288 ppm. In the case of a 50% syngas-50% hydrogen fueling engine, the mean exhaust gas temperature decreases from 1283 K to 1187 K leading to a decrease in NOx concentration from 3268 ppm to 2231 ppm. The dual injection has the advantage of lower NOx emission, whereas the blend injection has the advantage of higher efficiency